1983
DOI: 10.1002/1097-0142(19830815)52:4<661::aid-cncr2820520416>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic neuroectodermal tumor of infancy a review of seven cases

Abstract: The melanotic neuroectodermal tumor of infancy (MNTI) is a rare, usually benign, pigmented neuroectodermal tumor which most often involves the maxilla. The authors reviewed seven cases of MNTI, with patient ages of our patients ranged from nine weeks to 18 months; six of the seven were less than six months old at initial diagnosis. Four patients were males, and all were white. One tumor each was located in the femur, the temporal bone, and the epididymis; the remaining lesions occurred in the maxilla. Three of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 17 publications
5
69
0
3
Order By: Relevance
“…Its free form found in great quantity is regarded as a marker of the neuroectodermal tumours. The disappearance of high rates of VMA after MNTI surgical removal confirms the neurocristopathic hypothesis (6). Nevertheless, a significant number of cases of MNTI associated with normal levels of VMA appear in the literature.…”
Section: Etiopathogenic Hypothesessupporting
confidence: 68%
See 1 more Smart Citation
“…Its free form found in great quantity is regarded as a marker of the neuroectodermal tumours. The disappearance of high rates of VMA after MNTI surgical removal confirms the neurocristopathic hypothesis (6). Nevertheless, a significant number of cases of MNTI associated with normal levels of VMA appear in the literature.…”
Section: Etiopathogenic Hypothesessupporting
confidence: 68%
“…This lesion is regarded as benign, although it can show locally aggressive behaviour, with gradual invasion of the surrounding bone and the sinuses. Recurrences have been described after surgical excision, and in exceptional cases, metastasis have been discovered (6). The rate of recurrence has been estimated at 15% and the rate of malignant transformation at 6.6% (4).…”
Section: Discussionmentioning
confidence: 61%
“…Pigmentation may or may not be seen in the overlying soft tissue. This condition is generally found in patients under the age of 1 year, usually without predilection for sex [1,8,10,11], although in some review studies of cases described in the literature, we observed a slight predilection for the male sex [1,8,[12][13][14]. In spite of being locally invasive, these tumors are generally described as being benign.…”
Section: Discussionmentioning
confidence: 99%
“…The local recurrence rate following excision ranges from 10% to 15%, although it has been reported as high as 45% (11,12,25,41,42). Shaia et al (38) examined the risk of recurrence over the past 20 years and found that it did not differ from historical data since the tumour was first diagnosed 90 years previously.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%